Study on the Impact of Technological Innovation Capabilities on Competitive Advantage and Firm Performance in the Automotive Industry in Malaysia: A Conceptual Framework - Faridah, Taju Rahim; Yuserrie, Zainuddin (JSRAD, 2015)
This paper focuses on applying the resource-based view (RBV) of firms to explain performance in the automotive industry in Malaysia. Specifically, we based our research on the comprehensive framework of RBV and reviewed previous empirical researchers to investigate the relationship between technological innovation capabilities (TIC), competitive advantage and firm performance in the automotive industry in Malaysia. The conceptual model using Partial Least Squares (PLS) has been proposed. Based on the proposed conceptual framework and reviewed, research hypotheses are being developed. The conceptual framework of this paper will be used at the preliminary stage of the research on TIC that can be expected to contribute in the development of automotive industry in Malaysia.